Competitividad regional de los e-sports en Latinoamérica: el caso de League of Legends - Ramírez Alvarado, Marco Antonio (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
The objective of the research was to determine to what extent the variables innovation, infrastructure, market, institutions and technology promoted the regional competitiveness of E-sports or electronic sports in the Latin American region. It was unleashed that for the investigation only the E-sports called League of Legends was analyzed. E-sports are an activity in which one or more players compete in an amateur or professional manner using a video game. These competitions can be carried out in person or remotely. As for the case of the Latin American region, E-sports are in a stage of medium or initial development in many of the cases. To carry out the research, a questionnaire was developed and applied, obtaining as a result that the variables mentioned, all of them, have a direct and positive connection on the regional competitiveness of E-sports in the Latin American region. Based on the results obtained, some recommendations were presented to improve the regional competitiveness of E-sports in the Latin American region.

La investigación tuvo como objetivo determinar en qué medida las variables innovación, infraestructura, mercado, instituciones y tecnología afectan a la competitividad regional de los E-sports o deportes electrónicos en la región Latinoamérica. Se desataca que para la investigación sólo se analizó el E-sports llamado League of Legends. Los E-sports son una actividad en la que uno o más jugadores compiten de manera amateur o profesional haciendo uso de un videojuego. Estas competencias pueden llevarse de manera presencial o remota. En cuanto al caso de la región Latinoamérica, los E-sports se encuentran en una etapa de desarrollo medio o inicial en muchos de los casos. Para llevar a cabo la investigación se elaboró y aplicó un cuestionario, obteniendo como resultado que las variables mencionadas, todas ellas, tienen una correlación directa y positiva sobre la competitividad regional de los E-sports en la región Latinoamérica. Con base en los resultados obtenidos se presentaron algunas recomendaciones para mejorar la competitividad regional de los E-sports en la región Latinoamérica.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias del Desarrollo Regional
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2022-0555; Competitividad; E-sports; Tecnología; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6766